Exposure to Mild Steel Welding and Changes in Serum Proteins With Putative Neurological Function-A Longitudinal Study - Anda R. Gliga; Tahir Taj; Karin Wahlberg; Thomas Lundh; Eva Assarsson; Maria Hedmer; Maria Albin; Maria Albin; Karin Broberg; Karin Broberg (Frontiers Media S.A., 2020)
Welders are exposed to high levels of metal particles, consisting mainly of iron and manganese (Mn) oxide. Metal particles, especially those containing Mn can be neurotoxic. In this exploratory study, we evaluated associations between welding and expression of 87 putative neurology-related proteins in serum in a longitudinal approach. The study cohort from southern Sweden included welders working with mild steel (n = 56) and controls (n = 67), all male and non-smoking, which were sampled at two timepoints (T1, T2) 6-year apart. Observed associations in the longitudinal analysis (linear mixed models) were further evaluated (linear regression models) in another cross-sectional sample which included welders (n = 102) and controls (n = 89) who were sampled only once (T1 or T2). The median respirable dust levels for welders after adjusting for respiratory protection was at T1 0.6 (5-95 percentile: 0.2-4.2) and at T2 0.5 (0.1-1.8) mg/m3. The adjusted median respirable Mn concentration was at T2 0.049 mg/m3 (0.003-0.314) with a Spearman correlation between adjusted respirable dust and respirable Mn of rS = 0.88. We identified five neurology-related proteins that were differentially expressed in welders vs. controls in the longitudinal sample, of which one (nicotinamide/nicotinic acid mononucleotide adenylyltransferase 1; NMNAT1) was also differentially expressed in the cross-sectional sample. NMNAT1, an axon-protective protein linked to Alzheimers disease, was upregulated in welders compared with controls but no associations were discerned with degree of exposure (welders only: years welding, respirable dust, cumulative exposure). However, we identified five additional proteins that were associated with years welding (GCSF, EFNA4, CTSS, CLM6, VWC2; welders only) both in the longitudinal and in the cross-sectional samples. We also observed several neurology-related proteins that were associated with age and BMI. Our study indicates that low-to-moderate exposure to welding fumes is associated with changes in circulating levels of neurology-related proteins.